(untitled) (Papeles, 2023)
Introduction: Reading comprehension is a fundamental tool for learning and personal development of individuals. For these reasons the aim of this work is focused on analyzing the perceptions of students belonging to six technical secondary schools from different urban and rural sectors of Ciudad Juárez, Chihuahua, Mexico. The foregoing, based on their academic and personal experiences lived at school, in the family and their sociocultural contexts. Methodology: For this reasons, 56 second-grade students with difficulties in reading comprehension participated in this research. A qualitative phenomenological study was carried out. For data collection, with open and semi-structured question guides, 36 a depth interviews were conducted, nine focus groups and the student’s journal were implemented. Results and discussion: The results showed that most of the students: they are not familiar with the concept of reading comprehension. Their reading preferences focus on topics according to their age and personal interests more than in academics contents. They perceive school as a place of shelter, to personal overcome themselves and to build friendships. They conceive the Reading class as boring, which is related to the methodologies implemented by the teachers. They dislike those teachers who continue to practice traditional teaching methods. Finally, they develop in contexts where violence is part of their daily lives. Conclusions: It is concluded that the students perceive that reading comprehension is not a relevant issue for their stage, this being generated from the violent environments and with multiple sociocultural problems that they experience.